Functional respiratory imaging assessment of glycopyrrolate and formoterol fumarate metered dose inhalers formulated using co-suspension delivery technology in patients with COPD. (May 2020) - De Backer, Wilfried; De Backer, Jan; Verlinden, Ilse; Leemans, Glenn; Van Holsbeke, Cedric; Mignot, Benjamin; Jenkins, Martin; Griffis, Dianne; Ivanov, Stefan; Fitzpatrick, Jane; St Rose, Earl; Martin, Ubaldo J.; et al.
Background: Functional respiratory imaging (FRI) is a quantitative postprocessing imaging technique used to assess changes in the respiratory system. Using FRI, we characterized the effects of the long-acting muscarinic antagonist (LAMA), glycopyrrolate metered dose inhaler (GP MDI), and the long-acting β2 -agonist (LABA), formoterol fumarate metered dose inhaler (FF MDI), on airway volume and resistance in patients with moderate-to-severe chronic obstructive pulmonary disease. Methods: Patients in this phase IIIb, randomized, double-blind crossover study received twice-daily GP MDI (18 μg) and FF MDI (9.6 μg). Primary endpoints were specific (i.e. corrected for lobar volume) image-based airway volume (siVaw) and specific image-based airway resistance (siRaw), measured using FRI. Secondary and other endpoints included additional FRI, spirometry, and body plethysmography parameters. Postdose efficacy assessments were performed within 60–150 min of dosing on day 15. Results: A total of 23 patients were randomized and 19 completed both treatment periods. GP MDI and FF MDI both achieved significant improvements from baseline to day 15 in siVaw [11% ( p  = 0.0187) and 23% ( p  < 0.0001) increases, respectively] and siRaw [25% ( p  = 0.0219) and 44% ( p  < 0.0001) reductions, respectively]. Although, on average, improvements were larger for FF MDI than GP MDI, some individuals displayed greater responses with each of the two treatments. These within-patient differences increased with airway generation number. Spirometry and body plethysmography endpoints showed significant improvements from baseline in inspiratory capacity for both treatments, and numeric improvements for other endpoints. Conclusion: Both GP MDI and FF MDI significantly improved siRaw and siVaw at day 15 versus baseline. FRI endpoints demonstrated increased sensitivity relative to spirometry and body plethysmography in detecting differences between treatments in a small number of patients. Intra-patient differences in treatment response between the LAMA and the LABA provide further support for the benefit of dual bronchodilator therapies. ClinicalTrials.gov registration number: NCT02937584 The reviews of this paper are available via the supplemental material section.